Have Vultures Left the Battlefield? Scavengers and War in Greek Historiography - Kostuch, Lucyna (Histos, 2018)
There is much talk in the Iliad of dead warriors abandoned to vultures, and information about vultures tormenting armies can be found in ancient works from various literary genres. Surprisingly, however, when we look at the battle depictions of Greek historians, we do not find vultures portrayed as lurking on the battlefield. The question that arises is why the Greek historians did not adopt this significant element of the Homeric depiction of war. This article will attempt to explain, from various different perspectives, the absence in Greek historiography of vultures and other ferocious beasts in the Homeric role.